Elevated Mortality Among People Experiencing Homelessness With COVID-19. (4th June 2021) - Leifheit, Kathryn M; Chaisson, Lelia H; Medina, Jesus A; Wahbi, Rafik N; Shover, Chelsea L
Abstract: We reviewed publicly available data from major US health jurisdictions to compare severe acute respiratory syndrome coronavirus 2 case fatality rates in people experiencing homelessness with the general population. The case fatality rate among people experiencing homelessness was 1.3 times (95% CI, 1.1–1.5) that of the general population, suggesting that people experiencing homelessness should be prioritized for vaccination.